Kurangnya Pemahaman Pasien Dalam Memahami Kaidah Hukum Informed Consent Dalam Praktik Dokter - Moh Irsyad Hanif (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The patient's lack of understanding regarding informed consent in doctors' medical actions is motivated by several factors. Informed consent is a process as well as the result of an effective communication between the patient and the doctor/dentist and not just the signing of the consent form. The relationship between doctors, hospitals and patients or what is known as the therapeutic transaction is generally the origin of conflict. Conflict can occur when the parties do not carry out their roles as expected by the other party. This requires learning or educating patients regarding informed consent through the information media platform provided at the hospital. This journal discusses the reasons why many patients do not understand the contents of informed consent.